PENGARUH DAU, JUMLAH PENDUDUK, IPM DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI DI MALUKU UTARA - ERI SETYOWATI; RIFKI KHOIRUDIN (LP2MTBM MAKARIOZ, 2022)
The results of the study partially show that, (1) the general allocation fund has no effect on economic growth, (2) thepopulation has a positive and significant effect on economic growth, (3) the human development index has a positive andsignificant effect on economic growth, (4 ) Capital expenditure has no effect on economic growth. While the results ofsimultaneous research, namely general allocation funds, population, human development index, and capital expendituressimultaneously have a significant influence on economic growth. Researchers took this title by looking at previousresearchers, one of which is research from Astria (2014) entitled